Analysis of solar radiation measurements at EI-Kharga (250 N, 300E), Egypt - SALEM, A. I.; GABR, M.; SALEEM , S.; BASSYOUNI, A. H. (MAUSAM, 1993)
Daily global solar. radiation data of EI-Kharga for five year (1984-88) have been processed, analysed and classified into eight radiation levels spaced at an interval of 4.19 MJ m-2 day-l. Mean annual monthly and daily total the diurnal variation, and the frequency distribution of daily totals of global solar radiation are computed and discussed. A correlation between the hourly values of the clearness and diffuse indices were obtained and the recommended correlation ,equations were also given. The, results presented in this analysis are encouraging since they Indicate that periods of several days of low radiation of less than 8.38 MJm , day are rare. This In turn means that the weather sequence variations are not expected, to be of great Importance when considering the storage problems Involved In solar process design.